The Effects of Different Induction Chemotherapy Cycles and Adjuvant Chemotherapy on the Survival Outcomes of Patients With Locally Advanced Nasopharyngeal Carcinoma - Liao, Shu; Diao, Yunlian; Ling, Qingyuan; Xiong, Zhijuan; Deng, Wenxin; Zhang, Ping; Zhang, Congkai; Ying, Ying; Zhong, Xiaojun; Zhang, Wei (Frontiers in Oncology, 2022)
Objective: This study investigated whether differences in induction chemotherapy (IC) cycle number and adjuvant chemotherapy (AC) affect survival outcomes in patients with locally advanced nasopharyngeal carcinoma (LA-NPC). Methods: The survival outcomes of 386 consecutive LA-NPC patients treated between January 2015 and March 2018 were retrospectively analyzed. Univariate and multivariate analysis were used to compare treatment groups defined by IC< 3 or ≥3 IC cycles followed by radiotherapy with or without AC (i.e., IC<3+AC, IC<3+non-AC, IC≥3+AC, and IC≥3+non-AC groups). Results: The median follow-up time was 53 months (range: 2-74 months) and median number of IC cycles was 2 (range: 1-6 cycles). The 3-year overall survival (OS) rate was significantly higher in patients with IC≥3 cycles compared to IC＜3 cycles (95.7% VS 90.3%, P=0.020). Multivariate analysis indicated that the IC cycle number is an independent factor for OS (HR=0.326, P=0.007). Furthermore, patients in the IC＜3+AC group had a better OS rate than those in the IC＜3+non-AC group (91.6 % VS 79.1%, P=0.030), indicating AC positively affected OS in patients with IC<3. However, no significant difference in OS rate was found between IC≥3+non-AC and IC≥3+AC groups (92.1 % VS 94.6%, P =0.550). Conclusion: IC cycle number appears to be an independent prognostic factor for higher OS in LA-NPC patients who received ≥3 cycles. Sequential AC after IC plus radiotherapy may improve OS in patients with IC＜3 cycles.